KAJIAN LONCATAN HIDROLIK PADA KOLAM OLAK MODEL FISIK BENDUNGAN KRUENG SABEE KABUPATEN ACEH JAYA - Muslem, Muslem; Azmeri, Azmeri; Syamsidik, Syamsidik (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Hydraulic jump is a phenomenon that occurs in stilling basins from supercritical to subcritical conditions. The design of the Krueng Sabee dam aims to meet the needs of the people in the Aceh Jaya district. So this study aims to identify the behavior of hydraulic jumps that occur in energy dissipators in the form of jump height and energy dissipation to obtain an optimal design. The research method is a physical model study with an undistorted scale of 1:30. The energy dissipator used in this plan is the USBR IV stilling basin type. The discharge flowed on the physical model of the Krueng Sabee dam with return periods of Q2, Q5, Q10, Q25, Q50, Q100, and Q1000 years. Tests were carried out on 2 types of models, namely the Detail Engineering Design (DED) model series and the modified model series. In the modified model series, the addition of a 3 m high slope with a slope of 1:2, the elevation of the stilling pool was lowered to a depth of 3 m, and the addition of the length of the stilling pool was 4.8 m. The results of this study indicate that the modified series model is more optimal than the DED series model. The pattern of high jump and jump length increased against Froude numbers on the upstream jump showed a series of modified models better. The results of energy dissipation observations show that the modified model series is more competitive. The highest relative hydraulic jump ((y1-y2)/y1) that occurred in the modified model series was 19.40 (almost 3 times higher) than the highest ((y1-y2)/y1) model of the DED series model, which was 6.54. In the modified series, the farther Lj/y1 occurs the greater ∆E/y1 generated. On the other hand, there is a large decrease in relative energy dissipation (∆E/y1) with increasing relative hydraulic jump length (Lj/y1) in the DED series. The results of the analysis show a large decrease in ∆E/y1 to an increase in the ratio y1/y2 in both series of stilling basin models.